Effect of cold rolling and subsequent annealing treatments on fatigue behaviour and microstructure evolution of a high-mn TWIP steel - Zamani, Davood (2020)
A high-Mn TWIP steel represents excellent combination of ultimate tensile strength and ductility, but it have low yield strength. In particular, high yield strength is crucial for majority of the regularly encountered service conditions, like vehicle’s suspension and chassis. On the other hand, majority of the structural components are served at cyclic loading condition and low cycle fatigue performance is regarded to be significant in automobile durability analysis. Therefore, finding strategies to increase yield strength accompanied by great low cycle fatigue performance will go a long way towards upscaling TWIP steels to many industrial applications.